Elevated neutrophil-to-lymphocyte ratios correlate with increased clozapine concentration-to-dose ratios during titration - Bunichiro Onodera; Mutsumi Sakata; Kazuro Ikawa; Daisuke Kume; Naoki Horikawa; Hiroshi Komatsu; Takuhiro Yamaguchi; Hiroaki Tomita; Yuki Kikuchi (Schizophrenia)
Abstract Few cohort studies have examined the relationship between inflammation and increased clozapine blood levels. The purpose of this study was to investigate the relationship between the neutrophil-to-lymphocyte ratio (NLR), a marker of inflammation, and the clozapine concentration-to-dose (C/D) ratio during clozapine titration. We retrospectively investigated the medical records of all patients at Nozoe Hills Hospital who met the following criteria: 1) patients with schizophrenia who were first treated with clozapine between April 2020 and July 2024 and 2) patients for whom clozapine blood levels were measured for at least two consecutive weeks after the start of clozapine treatment. The study included 143 blood samples from 28 patients collected within 6 weeks of starting clozapine treatment. A linear mixed model with random intercepts was used to determine the correlation between the clozapine C/D ratio and NLR in samples repeatedly measured within an individual. Fixed effects for the C/D ratio included NLR, week, and the interaction between NLR and week. A significant fixed effect of NLR on C/D ratio was observed (estimate: 0.70; 95% confidence interval: 0.47–0.92; P < 0.0001). The fixed effect of NLR was attenuated over time due to a significant negative interaction between NLR and week. The fixed effect of NLR remained significant even after excluding the six patients who had fever during clozapine titration. This study suggests a positive correlation between the C/D ratio and NLR during clozapine titration. Our findings indicate that subclinical inflammation in the early titration phase affects the pharmacokinetics of clozapine.